The Shape of the World: What if Aesthetic Properties Were Real? - Sartwell, Crispin (The Nordic Journal of Aesthetics, 2011)
<!--StartFragment--> Perhaps we should entertain the idea that aesthetic properties are no less (but no more) objective than properties like weight or shape. Indeed, the weight and shape of something are themselves aesthetic properties of that thing. And we might speculate or (what the heck) assert that aesthetic properties are no more (but no less) socially constructed than size or material composition, for example. Indeed the size and material composition of something are aesthetic properties of it. We might, that is, live in an aesthetic universe, live embedded in an aesthetic reality. Then, for example, to give a full description of any thing or phenomenon, we would have to resort to aesthetic categories: perhaps there is no natural science, for example, without aesthetics, and vice versa. On a good day, the universe might really, actually, truly be beautiful <!--EndFragment-->